Reinstatement of rhipicephalus (Boophilus) australis (Acari: Ixodidae) with redescription of the adult and larval stages - Estrada Peña, Agustín (2012)
Rhipicephalus australis Fuller, the Australian cattle tick, is reinstated and the adults and larvae redescribed from material collected in Australia. This long ignored boophilid was previously known as R. microplus Canestrini for specimens reported in Australia and New Caledonia. The adults of R. australis are easily recognized by a combination of characters, such as the ventro-medial spurs in the palpal segments of the male, and the abundant, plumose, pale white setae on the dorsum of the female. Other details, such as coxal and adanal shields are more variable among different populations and may lead to incorrect determinations. Larvae of R. australis are clearly smaller than those of R. microplus. The use of principal components analysis on body measurements leads to a clear separation of larvae of both taxa. A phylogenetic analysis based on 12S- and 16S-rDNA gene sequences supports the conspecificity of the neotype material on which the reinstatement of the species is proposed, and of the specimens used for previous interspecific crosses. R. australis is now known to be present in Australia, New Caledonia, the island of Borneo, Philippines, Sumatra, Java, New Guinea, Cambodia, and Tahiti. Both R. microplus and R. australis coexist in some countries in southeastern Asia. Given the extreme importance of these ticks for the cattle industry, field data on their distribution in the region are required to know the actual range of these species and to understand the evolution of the group.